Take control of PDFpen5 v1.0 - Cohen, Michael E. (TidBITS Pub., 2010)
"Have you ever had to fill out and sign a PDF-based form? Or change the date on a PDF-based flyer? Comment on a document sent around your workplace as a PDF file? Scan a document to PDF and OCR the text? Smile's PDFpen 5 can perform these and many other PDF manipulations more easily than Adobe Acrobat, and at a fraction of the price. With clarity and humor, Take Control of PDFpen 5 explains precisely what you can do with PDFs using PDFpen and its big brother, PDFpenPro."--Resource description page.